Light-induced, carrier-mediated transport of tetracycline by Rhodopseudomonas sphaeroides. - Weckesser, J (1979)
Tetracycline accumulation by the phototrophic bacterium Rhodopseudomonas sphaeroides has been studied, using the fluorescence properties of the antibiotic and measuring uptake of [7- 3H]tetracycline. Accumulation was carrier mediated, with a Km of approximately 300 micronM. Efflux also appeared to be carried mediated, with a Km of 25 mM. Chlorotetracycline competitively inhibited tetracycline transport. The transport was energy dependent. Efflux occurred during the influx process, and an energy-requiring steady state was reached when influx balanced efflux. Transport was inhibited by metabolic inhibitors such as antimycin A, cyanide, and iodoacetate. Proton conductors such as carbonylcyanide m-chlorophenyl hydrazone were strongly inhibitory. Efflux was not energy dependent. Efflux is partially blocked by mercuric ions and completely blocked by an external pH of 9 to 11. Although efflux rates increased continuously with lowering of the pH, influx rates have a sharp maximum at pH 7.